2019
DOI: 10.1111/jre.12664
|View full text |Cite
|
Sign up to set email alerts
|

The influence of high‐dose systemic zoledronate administration on osseointegration of implants with different surface topography

Abstract: Aim To evaluate the influence of systemic zoledronate administration on the osseointegration of titanium implants with different surface topography in rat maxillae. Methods Twenty Sprague‐Dawley rats were divided into two groups—test (bisphosphonate) and control (healthy). Bisphosphonate administration began three weeks prior to implant placement, and the animals received zoledronate (66 μg/kg) three times per week. Forty endosseous implants with a moderately rough (20 implants) or a turned surface (20 implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…However, it could be shown in a preclinical study, that both materials osseointegrated equally, so without significant difference [ 31 ]. Hou et al [ 32 ] evaluated the osseointegration of titanium implants in rats with systemic zoledronate administration and found that bone-to-implant contact was negatively influenced by the drugs. Similarly, Dikicier et al [ 33 ] demonstrated that there is an unfavorable implant osseointegration regarding the BIC value after administering systemic zoledronic acid in rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, it could be shown in a preclinical study, that both materials osseointegrated equally, so without significant difference [ 31 ]. Hou et al [ 32 ] evaluated the osseointegration of titanium implants in rats with systemic zoledronate administration and found that bone-to-implant contact was negatively influenced by the drugs. Similarly, Dikicier et al [ 33 ] demonstrated that there is an unfavorable implant osseointegration regarding the BIC value after administering systemic zoledronic acid in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical studies have already been performed to study the effect of such treatments on peri-implant bone regeneration in both healthy and osteoporotic animal models [9,18,19,[33][34][35]. Despite existing evidence that single treatment with BPs or simvastatin can enhance bone formation around dental implants in healthy and osteoporotic animal models, only limited work has been dedicated toward the effect of combined administration of anti-resorptive and anabolic agents [22][23][24][25]36,37]. In addition, there is a wide variation in the route of administration of such pharmacological agents, the timing in relation to osteoporosis induction and subsequent implant placement, as well as implantation time.…”
Section: Discussionmentioning
confidence: 99%
“…Novel biomaterials in the oral microenvironment need to be studied for extended periods to evaluate cytocompatibility. Such responses are tested under in vitro conditions over long time intervals using cell viability assays, expression of select proteins, such as collagen type 1 and alkaline phosphatase, the mineralization of dentin matrix, and the inflammatory cytokine expression in dental pulp cells, gingival fibroblasts, and osteoblast cells. Ivanovski and colleagues have performed such extensive studies on biocompatibility of implants. , In one study, the osseointegration of commercially available hydrophobic SLA and hydrophilic SLActive implants were compared upon placement into augmented maxillary sinuses of sheep for up to 4 weeks . It was found that the hydrophilic implant surface had a significantly greater percentage of bone to implant contact and tissue composition than the hydrophobic implants.…”
Section: Implant Characteristicsmentioning
confidence: 99%